PENGARUH AUDITOR CLIENT TENURE, REPUTASI AUDIT DAN UKURAN PERUSAHAAN TERHADAP AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Hutabarat, Clara P. Georgina; Sudjiman, Lorina Siregar (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2022)
This study aims to analyze the effect of auditor client tenure, audit reputation and company size on going concern audits in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2019-2021. This research method uses quantitative methods by performing data analysis techniques used in this study are descriptive statistics, multicollinearity test, overall fit model test, model feasibility test, coefficient of determination, classification matrix test and logistic regression significance test. Sample data obtained from as many as 27 companies with a total sample of 81. The results of this study indicate that hat (1) Auditor Client Tenure has no significant effect on Going Concern Audit (2) Audit reputation does not have a positive effect on Going Concern Audit, and (3) Company Size has no effect on Going Concern Audit.